2017
DOI: 10.1007/s00268-017-4202-5
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curve Characteristics for Caesarean Section Among Associate Clinicians: A Prospective Study from Sierra Leone

Abstract: While gaining experience, the operation time of associate clinicians significantly reduced during the first 15 caesarean sections. Estimated bloodloss is not related to trainees experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…The mean operating time decreased from 79.6 min to 58.4 min for the 4th cohort, before stabilizing around 49.2 min during the 31st-35th herniorrhaphies. This finding was in line with near similarly designed studies that reported greatest decline in operating time early in the learning curve of trainees performing cesarean sections [14], and a cumulative sum control chart (CUSUM) analysis demonstrating similar operating times between surgical residents and surgeons after performing 37-42 tension-free mesh repairs [25]. In addition, we demonstrated that trainees who dropped out, or failed to perform 55 herniorrhaphies during the three years of surgical training, had a significantly different trajectory on the surgical learning curve.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The mean operating time decreased from 79.6 min to 58.4 min for the 4th cohort, before stabilizing around 49.2 min during the 31st-35th herniorrhaphies. This finding was in line with near similarly designed studies that reported greatest decline in operating time early in the learning curve of trainees performing cesarean sections [14], and a cumulative sum control chart (CUSUM) analysis demonstrating similar operating times between surgical residents and surgeons after performing 37-42 tension-free mesh repairs [25]. In addition, we demonstrated that trainees who dropped out, or failed to perform 55 herniorrhaphies during the three years of surgical training, had a significantly different trajectory on the surgical learning curve.…”
Section: Discussionsupporting
confidence: 89%
“…In the context of medical education, learning curves based on serial evaluation of operation-specific outcomes are thought to provide insight about the progress of a trainee [12,13]. While it was demonstrated that the operating time of ACs decreased significantly during their first 15 cesarean sections and then gradually stabilized [14], yet for other essential surgical procedures, the time until competency is reached is unknown.…”
mentioning
confidence: 99%
“…In Ghana, most inguinal hernia repairs are performed by medical officers, who are doctors with no formal training in surgery or any other specialized field . Previous studies have demonstrated that nonphysician clinicians can perform surgical procedures, including cesarean section and laparotomy, with similar results compared with surgical specialists . However, the safety and effectiveness of task sharing of surgical care with doctors without specific surgical training is not well described.…”
Section: Introductionmentioning
confidence: 99%
“…Closely related to training is human resource development. Several of the articles report positive experiences with task sharing, such as performance of safe cesarean sections by clinical officers in Sierra Leone [1,6,8,9]. These articles give further support for the viability of task sharing to increase access to surgical care, especially in poorer and more remote areas.…”
mentioning
confidence: 88%